The Extent of Implementation of Disaster Risk Reduction and Management in The Third District of Negros Oriental - Catarata, Annabelle T.; Villa, Elizabeth B. (Future Science / FSH-PH Publications, 2024)
his study aimed to assess the extent of implementation of Disaster Risk Reduction Management (DRRM) and the extent of stakeholder participation in times of disaster towards the development of a comprehensive community-based Disaster Risk Reduction Management (DRRM) strategic manual. This study employed a descriptive comparative research design utilizing survey methodology. The study was conducted in the Third District of the Province of Negros Oriental. The respondents were LGU officials, PNP, DRRM Coordinators, SK officials, barangay officials, and local residents and were selected using a stratified random sampling technique. The major tool used in this study is a survey questionnaire adopted from the Provincial Disaster Risk Reduction Plan manual. Data were analysed using weighted mean and one-way analysis of Variance (ANOVA). The study found that people are more proactive in preventing disasters than recovering from them. The poor performance of respondents in Disaster Rehabilitation and Recovery (DRRM) was attributed to a lack of expertise and resources. The DRRM program's effectiveness still needs to be explored; hence, there is an urgent need for further study and evaluation to measure its impact. Communities often lack the means and capacity to respond effectively, emphasizing the need for empowering and involving local populations in disaster management. Insufficient resources, capacity, and collaboration between stakeholders hinder the implementation of disaster management programs, resulting in inadequate results and a loss of confidence in the government's ability to address disaster management needs. An internal disaster response plan should be in place in every barangay and activated during and immediately after disasters. When chaos and devastation from a disaster demand capability beyond those that barangays can afford, Local Government Units (LGUs) and the National Government are supposed to respond. Designated Barangay Disaster Response Teams and volunteers may also help.